CONTENT, CRITERIA AND PRINCIPLES OF USE OF ELECTRONIC INFORMATION EDUCATIONAL RESOURCES IN BIOLOGY EDUCATION IN GENERAL EDUCATION SCHOOLS - SANAYEVA MUNISA ILAMONOVNA (The Bioscan, 2025)
In this article, the issues of wide introduction of electronic information educational resources to educational processes, improvement of scientific and methodical provision of electronic information educational resources and their effective use are highlighted, and the educational system is based on advanced foreign and national experiences. on the basis of improvement, special importance is attached to the creation and implementation of a new generation of electronic information technologies for the educational system. Also, opinions on the content, criteria and principles of the use of electronic information educational resources, the organization of biology education in general education schools on the basis of electronic information educational resources and the improvement of educational efficiency are provided.